Penyelesaian Sengketa Batas Tanah melalui Mediasi di Luar Pengadilan Demi Tercapainya Win-Win Solution di Kabupaten Boyolali - Broto Laksito, FX. Hastowo; Pradoto, Waluyo Slamet; Sunarto, Kesya Zhalibina (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The purpose of this service is to find out how to resolve land boundary disputes through mediation to achieve a win-win solution and what obstacles or obstacles arise in the implementation of land boundary dispute resolution through mediation. The method of community service is by means of lectures and discussions. Settlement of legal problems, especially land boundary disputes, has been accommodated by the state which has been outlined in national regulations through alternatives in court, namely filing a lawsuit and outside of court through mediation efforts. Of course, each route has advantages and disadvantages. A lawsuit in court results in a party winning or losing, while mediation outside of court results in neither party being harmed. Obstacles or barriers that arise in the implementation of Land Boundary Dispute Resolution through Mediation are the difficulty of uniting the desires and interests of both parties as well as the nature of not wanting to give in and feeling that each of them is the most right. However, mediation efforts require the skills of a mediator or intermediary to find solutions to problems that occur. The willingness of the parties to give in to each other and reduce each other's demands is an important key to achieving the goal of common good and prosperity so that no party feels disadvantaged.